1979
DOI: 10.1007/bf00347910
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of C3 and C4 grasses and carbon isotope discrimination along an altitudinal and moisture gradient in Kenya

Abstract: More than 500 species of the Poaceae are found in Kenya, East Africa. Eighteen of twenty-seven tribes are exclusively (except the Paniceae and Danthonieae) of the C photosynthetic type. A floristic analysis of low altitude grasslands suggests that nearly all species at these low altitudes are of the C photosynthetic type. At high altitudes, however, nearly all grasses are of the C photosynthetic type. Open grassland vegetation was sampled along a transect from arid low altitude sites to the top of Mt. Kenya in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
242
2
4

Year Published

1983
1983
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(267 citation statements)
references
References 36 publications
19
242
2
4
Order By: Relevance
“…C 4 grasses are more frequent in drier areas and C 3 grasses are more frequent in wetter areas. Tieszen et al (1979) found a highly significant correlation between the relative abundance of C 4 grasses and estimates of available soil moisture along a transeet in Kenya. These data were collected along an elevational transect and thus may reflect an interacting effect of decreasing temperature with increasing elevation and soil moisture.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…C 4 grasses are more frequent in drier areas and C 3 grasses are more frequent in wetter areas. Tieszen et al (1979) found a highly significant correlation between the relative abundance of C 4 grasses and estimates of available soil moisture along a transeet in Kenya. These data were collected along an elevational transect and thus may reflect an interacting effect of decreasing temperature with increasing elevation and soil moisture.…”
Section: Discussionmentioning
confidence: 86%
“…Multivariate analyses of the abundance of C 3 and C 4 grasses and herbs of North America have indicated that high moisture availability and low temperatures are strong correlates of relative C 3 abundance (Teeri and Stowe 1976;Stowe and Teeri 1978). Large-scale elevational transects in Wyoming (Boutton et al 1980), Kenya (Tieszen et al 1979), and Costa Rica (Chazdon 1978) show, with increasing elevation, a transition from C 4 to C 3 as the predominant photosynthetic pathway. Both drought stress and temperature tend to decrease with increasing elevation in these studies.…”
Section: Introductionmentioning
confidence: 97%
“…We therefore suppose that water stress controls the d 13 C pattern of plants below the breakpoint suggestive of a precipitation threshold, i.e., the less water availability the heavier d 13 C of plants, which in turn is translated into community level d 13 C, and recorded in SOM and soil n-alkanes. There is also a possibility of more contributions of C 4 plants at lower arid altitudes that likewise leads to increasing d 13 C with decreasing altitude, as has been found in many low altitude mountain areas [e.g., Tieszen et al, 1979;Bird et al, 1994;Cabido et al, 1997]. Gongga.…”
Section: Discussionmentioning
confidence: 95%
“…The C4 pathway was present in East Africa by at least the middle Miocene Morgan et al, 1994), and there was a global expansion of C4 biomass between 8-6 Ma (Cerling et al, 1997(Cerling et al, , 1998. C3 grass-dominated vegetation belts occur in equatorial Africa today only above 2,700•3,000 m (e.g., Tieszen et al, 1979;Livingstone and Clayton, 1980) and remained above 2200 m during glacial times (e.g., Bonnefille et al, 1990;Taylor, 1992). C3 photosynthesis may thus be treated as evidence of woody vegetation in interpreting paleosol 8 C values at Olduvai and other localities in tropical East Africa at low and intermediate altitudes since C4 grasses dominate the landscape, with C3 grasses restricted to cooler, shaded, forest understories or wetlands.…”
Section: Soil Stable Isotope Valuesmentioning
confidence: 99%